Quality of Patient Education Materials on Safe Opioid Management in the Acute Perioperative Period: What Do Patients Find Online?. Issue 1 (18th January 2019) - Kumar, Gunjan; Jaremko, Kellie M; Kou, Alex; Howard, Steven K; Harrison, T Kyle; Mariano, Edward R
Abstract: Objective: Guidelines on postoperative pain management recommend inclusion of patient and caregiver education on opioid safety. Patient education materials (PEMs) should be written at or below a sixth grade reading level. We designed this study to compare the readability of online PEMs related to postoperative opioid management produced by institutions with and without a regional anesthesiology and acute pain medicine (RAAPM) fellowship. Methods: With institutional review board exemption, we constructed our cohort of PEMs by searching RAAPM fellowship websites from North American academic medical centers and identified additional websites using structured Internet searches. Readability metrics were calculated from PEMs using the TextStat 0.4.1 textual analysis package for Python 2.7. The primary outcome was the Flesch-Kincaid Grade Level (FKGL), a score based on words per sentence and syllables per word. We also compared fellowship-based and nonfellowship PEMs on the presence or absence of specific content-related items. Results: PEMs from 15 fellowship and 23 nonfellowship institutions were included. The mean (SD) FKGL for PEMs was grade 7.84 (1.98) compared with the recommended sixth grade level ( P  < 0.001) and was not different between groups. Less than half of online PEMs contained explicit discussion of opioid tapering or cessation. Disposal and overdose risk were addressed more often by nonfellowship PEMs. Conclusions: Available online PEMs related to opioid management are beyond the recommended reading level, but readability metrics for online PEMs do not differ between fellowship and nonfellowship groups. More than two-thirds of RAAPM fellowship programs in North America are lacking readable online PEMs on safe postoperative opioid management.